2005
DOI: 10.1176/appi.ajp.162.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Male Body Image in Taiwan Versus the West: Yanggang Zhiqi Meets the Adonis Complex

Abstract: Taiwan appears less preoccupied with male body image than Western societies. This difference may reflect 1) Western traditions emphasizing muscularity and fitness as a measure of masculinity, 2) increasing exposure of Western men to muscular male bodies in media images, and 3) greater decline in traditional male roles in the West, leading to greater emphasis on the body as a measure of masculinity. These factors may explain why body dysmorphic disorder and anabolic steroid abuse are more serious problems in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
135
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(147 citation statements)
references
References 41 publications
6
135
0
3
Order By: Relevance
“…Terrestrial primates may be more vulnerable to sexual coercion than arboreal primates or birds; the larger body sizes of many terrestrial primates may have been favored in contexts of male-male contest competition (i.e., fighting), but can incidentally or adaptively be used for coercive behavior of females too. In this vein, it has been noted that female assessments of human male secondary sexual characteristics such as muscle mass or voice pitch tend to favor less extreme phenotypes than are favored by males (Yang et al, 2005;Puts, 2010). These data are consistent with sexual conflicts of interest: males might favor more extremes of muscularity in contexts of male-male competition, but females prefer less extremes because male musculature could also be used for coercion.…”
Section: Sexual Conflictmentioning
confidence: 64%
“…Terrestrial primates may be more vulnerable to sexual coercion than arboreal primates or birds; the larger body sizes of many terrestrial primates may have been favored in contexts of male-male contest competition (i.e., fighting), but can incidentally or adaptively be used for coercive behavior of females too. In this vein, it has been noted that female assessments of human male secondary sexual characteristics such as muscle mass or voice pitch tend to favor less extreme phenotypes than are favored by males (Yang et al, 2005;Puts, 2010). These data are consistent with sexual conflicts of interest: males might favor more extremes of muscularity in contexts of male-male competition, but females prefer less extremes because male musculature could also be used for coercion.…”
Section: Sexual Conflictmentioning
confidence: 64%
“…reviewing scientific studies on that subject, we have found that marathonists and runners have been studied but individuals who practice strength training haven not [13][14][15] . On the other hand, vigorexy has often been studied on subjects who take anabolic steroids but has not been analyzed in specific groups concerning their psychological characteristics and comorbidity [16][17][18] . Frequency of weekly sessions and length of time of physical activities have also been disregarded.…”
Section: Introductionmentioning
confidence: 99%
“…The status of the huge masculine body has changed over the years (cf. Yang, et al, 2005). In the 1990s and especially in the beginning of 2000s, the negative effects of steroids and drug use were thoroughly investigated, and today there are controls at many gyms.…”
Section: The Subculture Of Bodybuildingmentioning
confidence: 99%